2019
DOI: 10.1097/md.0000000000017920
|View full text |Cite
|
Sign up to set email alerts
|

The preoperative platelet to albumin ratio predicts the prognosis of hepatocellular carcinoma patients without portal hypertension after liver resection

Abstract: There is little information concerning the predictive ability of the preoperative platelet to albumin ratio (PAR) in hepatocellular carcinoma (HCC) patients after liver resection. In the current study, we aimed to assess the prognostic power of the PAR in HCC patients without portal hypertension (PH) following liver resection.Approximately 628 patients were included in this study. A receiver operating characteristic (ROC) curve analysis was performed to evaluate the predictive value of the PAR for both recurre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 42 publications
0
14
0
Order By: Relevance
“…Liver fibrosis and the platelet-to-albumin ratio ( Figure 3B ) are important indicators of liver inflammation, which results in impaired antitumor immune response ( 5 , 32 ). Therefore, the association between TBK1 expression and degree of immune infiltration in HCC was further investigated in this study.…”
Section: Resultsmentioning
confidence: 99%
“…Liver fibrosis and the platelet-to-albumin ratio ( Figure 3B ) are important indicators of liver inflammation, which results in impaired antitumor immune response ( 5 , 32 ). Therefore, the association between TBK1 expression and degree of immune infiltration in HCC was further investigated in this study.…”
Section: Resultsmentioning
confidence: 99%
“…Yet, present outcomes seem, by all accounts, to be in good congruency with those previously reported for pancreatic adenocarcinoma, cholangiocarcinoma, hepatocellular carcinoma, and non-small cell lung carcinoma patients undergoing surgery. [18][19][20][21] Guo et al 21 in a group of 198 stage I-IV non-small cell lung cancer patients who underwent thoracic surgery found that the preoperative PAR>8.8 was an independent predictor of significantly worse median OS times (P<0.001). Likewise, in the largest ever PAR study, Li et al 20 reported that patients with high preoperative PAR (>4.8) had a higher recurrence risk and lower longterm survival chance than those with low PAR in a total of 628 hepatocellular carcinoma patients treated with liver resection.…”
Section: Discussionmentioning
confidence: 99%
“…[18][19][20][21] Guo et al 21 in a group of 198 stage I-IV non-small cell lung cancer patients who underwent thoracic surgery found that the preoperative PAR>8.8 was an independent predictor of significantly worse median OS times (P<0.001). Likewise, in the largest ever PAR study, Li et al 20 reported that patients with high preoperative PAR (>4.8) had a higher recurrence risk and lower longterm survival chance than those with low PAR in a total of 628 hepatocellular carcinoma patients treated with liver resection. The remaining two studies in pancreatic cancer and cholangiocarcinoma patients further confirmed the poor prognostic characteristic of the high preoperative PAR values in these tumor primaries, respectively.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, the prediction model of prognosis of the HCC combined with different in ammation factors has always been a hot issue [9,10,29,30]. Previous studies have examined GLR's prognostic ability in HCC [14,31], intrahepatic cholangiocarcinoma [32] and nonfunctional pancreatic neuroendocrine tumors [25].…”
Section: Discussionmentioning
confidence: 99%